(untitled) (GIST – Education and Learning Research Journal, 2018)
This paper explores self-plagiarism in three different articles that reported results of the same research project on reading in a foreign language. This article follows the qualitative research method and an exploratory case study was used. Results support that both inadequate paraphrasing and adequate paraphrasing were given. Regarding inadequate paraphrasing some similar words and ideas were found. On the other hand, using different authors in a specific idea, having different numbers of words in a common issue, and being versatile to present information might lead to adequate paraphrasing. Conclusions suggest that a dialog between editors and authors must be given in order to clear self-plagiarism up. Finally, conclusions also suggest that editors should consider the inclusion of some similar information in articles written by the same author or the same research members